China’s Social Credit System - Hu, William Zhengdong. author. aut Link
XIX, 161 p. 2 illus.
Keywords: This book offers theoretical and empirical insights into analyzing, measuring, and assessing the political power of the Chinese state in shaping society. Focusing on the widely debated Social Credit System (SCS) and the sanctioned group known as laolai (deadbeats), it explores how national policies impact citizens – especially entrepreneurs – and how they respond in return. Political power has long been central to China’s development. In today’s market-driven economy, the fate of entrepreneurs continues to be shaped by the state and remains deeply intertwined with the nation’s future. As such, the evolving power dynamics between political authorities and entrepreneurs provide an efficient lens through which to understand China’s culture, economy, media, governmental efficacy, and state-society relation. The book addresses six key questions: (1) How do Chinese leaders and entrepreneurs help us understand the SCS and China’s trajectory? (2) How has the CCP shifted the SCS from supporting to controlling entrepreneurs? (3) How did entrepreneurs rise, why are they punished now, and how severe are the sanctions? (4) How have they resisted through legal and institutional means—and with what outcomes? (5) How are they perceived publicly amid negative media portrayals? (6) What do their interactions with the state reveal, from a Daoist perspective, about China’s future? The book is intended for policymakers, business leaders, scholars, and graduate students, speaking to the field of sociology, political economy, business, media, and China studies. It contributes to our understanding of the limits and reach of political power in contemporary China, the societal impacts of policy implementation, and the evolving role of entrepreneurs in shaping China’s future. William Zhengdong Hu, a Warwick Ph.D. and the first Chinese recipient of The Sociological Review Postdoctoral Fellowship in 2023–24, authored this book based on three years of mixed-method research, including 81 interviews and analysis of court judgments, official reports, and news articles. His interest lies in applying Daoist wisdom to discern the core forces shaping contemporary China’s development, especially the dynamic between politics and business.